Drought-induced responses of organic osmolytes and proline metabolism during pre-flowering stage in leaves of peanut (Arachis hypogaea L.) - Ming ZHANG; Li-feng WANG; Kun ZHANG; Feng-zhen LIU; Yong-shan WAN (Journal of Integrative Agriculture, 2017)
Abstract: Peanut (Arachis hypogaea L.), an improtant oil crop, usually encounters drought stress in the process of growth and development, especially at pre-flowering stage. In order to gain insight into the drought tolerance potentials based on osmolyte accumulation and metabolism of proline aspects of peanut, pot experiments were conducted with a split-plot design in Tai'an, Shangdong Province, China in 2013 and 2014. Pre-flowering drought (PFD) stress and optinum irrigation (control, CK) were served as the main plots and the two peanut cultivars Shanhua 11 and Hua 17 served as sub-plots. Shanhua 11 was drought-tolerant cultivar and Hua 17 was drought-sensitive. The content of soluble sugars, soluble protein, free proline and other free amino acids, the activities of enzymes involved in proline metabolism, and malondialdehyde (MDA) content and ion leakage were all investigated in the two cultivars at pre-flowering stage. Results showed that PFD stress significantly increased the levels of soluble protein, free proline and free amino acid, and increased Δ1-pyrroline-5-carboxylate synthetase (P-5-CS, EC 2.7.2.11) activity in the leaves of drought-tolerant and drought-sensitive cultivars. The activity of proline dehydrogenase (proDH) (EC 1.5.99.8) decreased under PFD stress in both cultivars. The leaves of the tolerant cultivar maintained higher increments of osmolyte levels, lower increments of MDA content and ion leakage, as well as a higher increased proportion of P-5-CS activity and higher inhibited proportion of proDH activity under water stress compared with the drought-sensitive cultivar. The study suggests that proline accumulation in peanut leaves under PFD can be explained by the higher enhanced activities of P-5-CS and higher inhibition of proDH. The results will provide useful information for genetic improvement of peanut under drought tolerance.